Development of stack component for thermoacoustic refrigerator using 3d printer - Nor Atiqah, Zolpakar; Normah, Mohd Ghazali (2021)
The development of thermoacoustic technology is motivated by the prospect that this technology will replace or reduce the dependence on the current vapor compression technology .The thermoacoustic refrigerator is an innovative alternative for clean cooling. The thermoacoustic effect is significant for intense sound waves in pressurized chamber. This effect can be utilized to produce a powerful engine, pulsating combustion, heat pumps, refrigerators, and mixture separators